Restraint in Warfare and Appamāda: The Concept of Collateral Damage in International Humanitarian Law in Light of the Buddha’s Last Words - Samarakoon, Bhagya (Contemporary buddhism, 2021)
In international humanitarian law (IHL), collateral damage to civilians caught in warfare is restrained through the rule of proportionality. The first part of this chapter explains how this increasingly controversial area is dependent on the perceptions, values and good faith of the military commander in the specific instance. In determining which Buddhist teachings can guide the mind in this grey area, the quality of appamāda, ‘heedfulness’, is significant. The Buddha refers to it several times in his sermons (suttas) and, most importantly, included it in his final words before his demise. The second part explores what the Buddha meant by appamāda and argues that the concept has a moral dimension useful in decision-making for Buddhists engaged in warfare. The third part discusses Emperor Ashoka to whom the monk Nigrodha preached the Appamāda Vagga. The change in Emperor Ashoka’s manner of ruling and conquering as manifested in his many edict inscriptions proves that Buddhist values can be practically applied by the laity, not just monastics. The fourth analyses how appamāda could guide the minds of Buddhists engaged in warfare, and proposes that this could be done through sermons (to transform intention) and meditation (to aid such transformation).